(untitled) (American Journal of Islam and Society, 2022)
We live in a time where ideas and principles are questioned, dissected, and contested at a dizzying rate. It can be difficult to decipher reason and proof from conjecture and avowal. Disjointed ideas and information are widely available without a necessary chain of transmission or reliable connection to sources of knowledge. In this confusing contemporary context, almost anyone can become a leader in thought, guiding naïve followers down unknown paths with unclear destinations. Yet, true thought leadership is that which is connected to the past and charts a clear, well-lit path forward toward an illumined future. Throughout time, there has been a legacy of truly brilliant thinkers whose genius is in communicating timeless wisdom in a powerful manner that speaks to the zeitgeist of their time. This ability allows them to make a significant impact on the hearts and minds of the people. The world lost one of these giants in thought leadership this past year. Professor Malik Babiker Badri was a man who not only innovated and developed novel ideas within his own area of expertise, but whose ideas had ripple effects well beyond the boundaries of his field of knowledge. Known to the academic and professional world as the “father of modern Islamic Psychology,” he also played a part in shaping massive cultural transformations that changed the world. These include the Black American experience, the epidemic of alcoholism, and the global AIDS crisis. Professor Badri brought to the world a cultural and spiritual revolution in the way many view their relationships to themselves, their societies, and their spirituality. Although several of his works have become seminal reads in the field of Islamic Psychology, and Islamic thought more generally, much of his great work remains unrecognized—perhaps because of his humility and lack of self-promotion. The time has come for the recognition of the significance of this man’s contributions which position him among the great thinkers of human history. This article charts the chronological and thematic development of Badri’s contributions over the course of his life and paints a picture of the significance of his work and its impact on the world.